PENGARUH KEBIASAAN MENGIKUTI PELAJARAN, KUNJUNGAN KE PERPUSTAKAAN, DAN KEBIASAAN MENGHADAPI UJIAN TERHADAP PRESTASI BELAJAR AKUNTANSI PADA MAHASISWA AKUNTANSI IKIP PGRI MADIUN - Anis Ridayani; Eva Vergowati; Evi Dwi Purnamasari (FIPA : Forum Ilmiah Pendidikan Akuntansi, 2013)
This study examined the effect of a habit to follow lessons, visits to the library, and the habits of the exam, while achievement obtained by the grade point average (GPA) in IKIP PGRI MADIUN. The data used are primary data collected using questionnaires and secondary data documentation number of students with a sample of accounting students IKIP PGRI MADIUN. The analysis tool used is multiple linear regression. The results of the analysis showed that together influence of habit to learn, visit Librarianship, and the habit of the exam affects student achievement accounting, and silmultan influence of habit to learn, visit Librarianship, and significant customs exams.